Utilization of tilapia, a trash fresh water fish. - Ismail, Mohamad Salleh; Zain, Asiah (1978)
Sixty-five percent (301 million) of the people living on insufficient diets are located in the Far East. Their daily protein supply decreased from 51.3 g/person in 1961 to 50.7 g/person in 1971. Fish is an important source of protein in South-East Asia but consumption is limited by price, supply, distribution and season, especially amongs the poor. Most fish comes from marine sources and in Malaysia, fish from aquaculture from less than one percent of the total, although there are 100000 acres of fresh water bodies suitable for aquaculture, in West Malaysia alone.